"Dropping Out is Not an Option": How Educationally Resilient First‐Generation Students See the Future. Issue 160 (6th April 2018) - Azmitia, Margarita; Sumabat‐Estrada, Grace; Cheong, Yeram; Covarrubias, Rebecca
Abstract: First‐generation college students (FGCS) often have different cultural values, practices, and goals from those of students from college‐going families. As they navigate college, FGCS coordinate these values, practices, and goals with those of their families, noncollege‐going friends, and communities. We draw on longitudinal and cross‐sectional studies of FGCS attending a public university in California to address three research questions: (1) What challenges do FGCS face in their transition to and through college?; (2) What resources do they use to surmount these challenges?; and (3) What is the association between FGCS' resources and challenges and their academic persistence and career goals? Results showed that FGCS who surmounted challenges and persisted toward graduation had emotional support from family and friends from home; developed supportive relationships with university peers, staff, and faculty; and believed that college would allow them to attain their future life and career goals.